The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/1120700019877174
|View full text |Cite
|
Sign up to set email alerts
|

Abductor muscle strengthening in THA patients operated with minimally-invasive anterolateral approach for developmental hip dysplasia

Abstract: Objective: In developmental hip dysplasia (DDH) patients, the chronic dislocation of the femoral head with respect to the true acetabulum determines muscle contracture and atrophy, particularly of the abductor muscles, and leads to secondary osteoarthritis (OA) with severe motor dysfunction, pain and disability. The correct positioning when a total hip replacement (THR) is performed is fundamental to the recovery of gait function. Also, inadequate rehabilitation of the abductor muscles for pelvic stabilisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
1
12
0
2
Order By: Relevance
“…Furthermore, we believe that preoperative and postoperative improvement in abductor muscle strength plays an important role in preventing postoperative dislocation in Crowe type IV patients, since it has been reported that an extended rehabilitation program for strengthening the gluteal muscles in DDH patients after THA can be effective. However, the rehabilitation protocol for Crowe type IV DDH patients needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we believe that preoperative and postoperative improvement in abductor muscle strength plays an important role in preventing postoperative dislocation in Crowe type IV patients, since it has been reported that an extended rehabilitation program for strengthening the gluteal muscles in DDH patients after THA can be effective. However, the rehabilitation protocol for Crowe type IV DDH patients needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…We compared gait analysis measurements, joint contact forces and muscle forces of the hip between a group of patients who performed the specific rehabilitation protocol and another group of patients who performed standard rehabilitation only, in the operated and contralateral limb. We tested the hypothesis that a higher improvement in clinical and functional outcome in patients after hip abductor strengthening, as shown recently [10], would result in differences in muscle and joint forces compared to patients who performed standard rehabilitation only.…”
Section: Introductionmentioning
confidence: 90%
“…Recently, we have evaluated the effects of a program of abductor exercises on a population of DDH patients through a randomized prospective study [10]. We found a significantly higher improvement in clinical and functional scores at follow-ups of a Study Group that performed a specific muscle strengthening program, compared to a Control Group that performed standard postoperative rehabilitation only.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations